Teachers’ authentic strategies to support student motivation - Radil, Amanda I.; Goegan, Lauren D.; Daniels, Lia M. (Frontiers in Education, 2023)
Most theories of motivation have largely developed from the work of scholars rather than the perspectives of teachers. This means that although researchers have many recommendations to guide the way teachers motivate students, there is little understanding of what teachers naturally do to support student motivation. The purpose of this study was to prioritize teachers’ perspectives by asking them, separate from theory, what they do to motivate students. Forty-two practicing teachers completed an open-ended online survey in which they described their personal strategies for motivating students. We used thematic analysis to identify nine themes: relevance, interest, relationships, effort, safe environment, goals, student self-regulated learning, delivery, and rewards. All of the strategies that teachers described align with recommendations motivation researchers would make with the exception of rewards, which from a research perspective are often discouraged. We discuss the results in light of motivation design principles and their relevance to partnering with teachers as a ubiquitous influence on student motivation.